Nutritional outcomes of Botswana infants and young children aged 6-24 months: a focus on birthweight, HIV-exposure, feeding practices and the role of caregivers, older family figures and healthcare workers - Chalashika, Paphani (2018)
Background: A better understanding of the nutritional status of infants and young children who are HIV-Exposed-Uninfected (HEU) and HIV-Unexposed-Uninfected (HUU) during their first 1000 days is a key to improving population health, particularly in sub-Saharan Africa. Methods: A mixed-methods approach (explanatory sequential design) was utilised to compare the nutritional status, feeding practices and determinants of nutritional status of HEU and HUU infants and young children residing in representative selected districts in Botswana. In addition, themes associated with perceptions of caregivers, older family figures and healthcare workers in achieving optimal nutritional outcomes in these infants and young children were identified. In the quantitative strand (413 infants and young children, 37.3% HIV-exposed) aged 6-24 months attending routine child health clinics were recruited. In the qualitative strand 25 caregivers, 9 older family figures and 10 healthcare workers were interviewed using a semi-structured questionnaire. Quantitative data including anthropometric, 24-hour dietary intake and socio-demographic data was collected. Anthropometric z-scores were calculated using 2006 WHO growth standards. Modelling of the determinants of malnutrition was undertaken using logistic regression. Qualitative data was analysed using an inductive, interpretive/latent thematic analysis approach. Results: Overall, prevalence of stunting, wasting and underweight were 10.4%, 11.9% and 10.2% respectively. HEU infants and young children were significantly more likely to be underweight (15.6% vs. 6.9%), (p<0.01) and stunted (15.6% vs. 7.3%), (p<0.05) but not wasted (p= 0.14) than HUU infants and young children. HEU infants and young children tended to be formula fed (89.4%) whereas HUU infants and young children tended to breastfeed (89.6%) for the first six months (p<0.001). In multivariate analysis, significant predictors of nutritional status were HIV exposure, birthweight, birth length, Apgar score and mother/caregiver’s education with little influence of socioeconomic status (p<0.05). Qualitative thematic analysis revealed four themes; when “free choice” is an illusion: mother’s infant feeding decisions; “These people are dangerous.” negotiating access to healthcare services; “caring is how I show my baby love”; “our culture, our heritage”. Conclusions: HEU infants and young children aged 6-24 months had worse nutritional status compared to HUU infants and young children. Notably, birthweight was the main predictor of undernutrition in this population and, therefore optimisation of infants and young children’ nutritional status should focus on the nutrition and health of women in the pre- and antenatal period. These interventions should focus on equipping caregivers with skills and knowledge but also address external factors such as influence of the older family figure, community norms and cultures and experiences associated with accessing healthcare services.